4 Channel Sterilizer Calibrator - Syafiq Naufal Syayakti; Endang Dian Setioningsih; Sumber Sumber (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Thermocouple (Thermocouple) is a type of temperature sensor used to detect or measure temperature through two types of metal conductors, whose working principle is that each end of a metal conductor is combined to create a